Personalizing Therapy in Advanced Non–Small Cell Lung Cancer - Villaruz, Liza C.; Burns, Timothy F.; Ramfidis, Vasilis S.; Socinski, Mark A. (Seminars in Respiratory and Critical Care Medicine, 2013)
The recognition that non–small cell lung cancer (NSCLC) is not a single disease entity, but rather a collection of distinct molecularly driven neoplasms, has permanently shifted the therapeutic landscape of NSCLC to a personalized approach. This personalization of NSCLC therapy is typified by the dramatic response rates seen in EGFR mutant NSCLC when treated with targeted tyrosine kinase inhibitor therapy and in ALK translocation–driven NSCLC when treated with ALK inhibitors. Targeted therapeutic approaches in NSCLC necessitate consideration of more invasive biopsy techniques aimed at providing sufficient tissue for both histological determination and molecular profiling in all patients with stage IV disease both at the time of diagnosis and at the time of disease progression. Comprehensive genotyping efforts have identified oncogenic drivers in 62% lung adenocarcinomas and an increasing proportion of squamous cell carcinomas of the lung. The identification of these oncogenic drivers and the triage of patients to clinical trials evaluating novel targeted therapeutic approaches will increasingly mold a landscape of personalized lung cancer therapy where each genotype has an associated targeted therapy. This review outlines the state of personalized lung cancer therapy as it pertains to individual NSCLC genotypes.
Keywords: non–small cell lung cancer; personalized therapy; oncogenic driver mutations